Togo : Request for Three; Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Togo. (IMF Staff Country Reports; Country Report ;, 2008)
Togo has made significant progress in advancing economic and political reforms under the Staff-Monitored Program (SMP). Important fiscal governance reforms have boosted tax revenues and helped expenditure control. The I-PRSP is designed to preserve macroeconomic stability while reviving economic growth and reducing poverty. The Poverty Reduction Growth Facility (PRGF) helped to consolidate macroeconomic stability, achieve fiscal and debt sustainability and pave the way for HIPC/MDRI debt relief. On account of a strong performance under the SMP, a fast reviving economy and achieving fiscal and debt sustainability, Togo requested a three-year arrangement with the IMF under the PRGF.